Footedness in world soccer: an analysis of France '98 - Carey, D. P.; Smith, G.; Smith, D. T.; Shepherd, J. W.; Skriver, J.; Ord, L.; Rutland, A. (Journal of Sports Sciences, 2001)
Most football players and coaches agree that players are capable of learning to use both feet with equal frequency and efficiency--that is, become 'two-footed'. There is also some consensus that two-footed play is associated with skill in individual players. If these assumptions are true, then the world's elite football players should be substantially less 'one-footed' than the rest of the population. To examine this issue, we quantified the pattern of foot use in a sample of 236 players from 16 teams in the 1998 World Cup (France '98). Our findings indicate that World Cup players are as right-footed as the general population (approximately 79%). The remaining players were largely left-footed and as biased towards the use of their preferred foot as their right-footed counterparts. Very few players used each foot with equal frequency. Remarkably, both left- and right-footed players were as skilled, on average, with their non-preferred foot as they were with their preferred foot, on the rare occasions when they used it. Therefore, it is unlikely that infrequent use of one foot compared to the other foot can be accounted for by skill differences between the feet. Players were most asymmetrical for set pieces; nevertheless, first touches, passes, dribbles and tackles were rarely performed with the non-preferred foot as well. Our results support a biological model of foot preference and performance, as well as demonstrating the usefulness of soccer for studies of lateral asymmetries.